Evaluasi Selang Waktu Pengukuran Ozon Dalam Proses Pengolahan AMDK Di PT. Tirta Sukses Perkasa Jember - Ega Nur’aini Fauziah; Prasetya Ramadhan; Silvia Oktavia Nur Yudiastuti (JOFE : Journal of Food Engineering, 2022)
The main use of water is as drinking water. PT. Tirta Sukses Perkasa is a company that produces Bottled Drinking Water (AMDK) with the trademark Club and Viand. A critical control point in the production of bottled drinking water is disinfection with ozone technology. Ozone monitoring at PT. Tirta Sukses Perkasa is held every 2 hours. To increase the effectiveness of production, a study was conducted to determine the effect of time interval monitoring ozone on the production process of bottled drinking water. The evaluation was carried out with an interval of 1 hour and 4 hours of monitoring. The interval of 1 hour and 4 hours was done to find out the efficient time for one work shift. One work shift is 8 working hours so in 1 hour the monitoring of ozone concentration is carried out 8 times/shift. The interval of 1 hour and 4 hours is done to find out the efficient time for 1 shift.The data processing method used is the t test. Based on the results of the evaluation of the tests carried out, it is known that the ozone in 1, 2, and 4 hours time intervals is not significantly different.